The New Literacies of Online Reading Comprehension : Future Directions - Julie Coiro (The Educational Forum, 2012)
Research in four areas has the potential to dramatically improve how practitioners address the challenges of integrating digital texts and tasks into their literacy curriculum. Advances in defi ning and measuring key componentsof online reading comprehension are rapidly emerging. In addition,instructional models, such acquisition of online reading comprehension, but teachers need access to sustained professional development that is aligned with their own learning goals.   Key words: new literacies, online inquiry, online reading comprehension, online reading, proficiency.
Keywords: compréhension; lecture numérique; littératie